Reasons for noncompliance with five-yearly screening flexible sigmoidoscopy - Viiala, C.; Olynyk, John (Dove Medical Press, 2008)
Objective: To determine factors influencing the low return rate observed in a program of flexible sigmoidoscopy for average risk screening for colorectal carcinoma. Methods: Flexible sigmoidoscopy-based screening of average risk 55-64 yr olds has been ongoing since 1995. Greater than 3400 primary and 1000 follow up screening examinations have been performed. Participants with a primary screen in 1997-1999 and eligible for rescreening in 2002-2004 were studied. A questionnaire assessing possible reasons for noncompliance was sent to subjects who did not attend the five year repeat screening. Results: 1672 primary screening flexible sigmoidoscopies were performed in 1997-1999 with 1362 being normal or having hyperplastic polyps only. The return rate was 45%: 48% of eligible males and 39% of eligible females had returned (p = 0.001 for difference). 709 questionnaires were mailed with a 50% response rate and 162 requests for repeat flexible sigmoidoscopy were generated. 27% of all respondents had undergone further bowel evaluation since the original normal sigmoidoscopy. Of eligible subjects who refused further screening, 65% did so because of concerns over procedural pain. Conclusions: Reasons for nonattendance relate to uptake of other bowel investigations and pain felt at initial screening. Return rate can be raised with ongoing prompting to attend screening. © 2008 Viiala and Olynyk, publisher and licensee Dove Medical Press Ltd.